2022
DOI: 10.1002/cncr.34452
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant cyclophosphamide‐based anti–graft‐vs‐host disease prophylaxis in patients with acute lymphoblastic leukemia treated in complete remission with allogeneic hematopoietic cell transplantation from human leukocyte antigen‐mismatched unrelated donors versus haploidentical donors: A study on behalf of the ALWP of the EBMT

Abstract: BACKGROUND:Both mismatched unrelated donor (MMUD) and haploidentical (haplo) transplantation are valid options in patients with high-risk acute lymphoblastic leukemia (ALL) lacking a matched donor. METHODS: The study compared the outcomes of adult patients with ALL in complete remission (CR) who underwent 9/10 MMUD versus haplo transplantation with posttransplant cyclophosphamide (PTCy) as graft-vs-host disease (GVHD) prophylaxis in 2010-2020. RESULTS: The study included 781 patients (MMUD, 103; haplo, 678). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Endothelial cell activation and damage may be due to different factors, such as the conditioning regimens, cytokines and chemokines produced by the injured tissues, the engraftment itself, the allogenicity, and also some drugs used during the transplant procedure, like granulocyte colonystimulating factor (G-CSF) (18) and immunosuppressant therapies (19,20). Cyclosporine A (CSA) is an immunosuppressive drug used as the standard GVHD prophylaxis in allo-HCT (21). However, it has been demonstrated that CSA has a clear adverse effect on the endothelium (19,22,23).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cell activation and damage may be due to different factors, such as the conditioning regimens, cytokines and chemokines produced by the injured tissues, the engraftment itself, the allogenicity, and also some drugs used during the transplant procedure, like granulocyte colonystimulating factor (G-CSF) (18) and immunosuppressant therapies (19,20). Cyclosporine A (CSA) is an immunosuppressive drug used as the standard GVHD prophylaxis in allo-HCT (21). However, it has been demonstrated that CSA has a clear adverse effect on the endothelium (19,22,23).…”
Section: Introductionmentioning
confidence: 99%